2011
DOI: 10.1007/s11199-010-9928-6
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Harassment and Psychosocial Maturity Outcomes among Young Adults Recalling Their First Adolescent Work Experiences

Abstract: The research questions addressed gender differences in the subjective appraisal of teens experiencing sexual harassment, and the psychosocial maturation of male and female teens appraising such events as threatening to their well-being. Using survey methodology, U.S. undergraduate women (n=316; 85% White Caucasian) and men (n=270; 85% White Caucasian) reported on their earliest formal work experiences (participants' average age was M=19.03, SD=1.87). Results indicated that women, more than men, were more upset… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
29
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(29 citation statements)
references
References 54 publications
(97 reference statements)
0
29
0
Order By: Relevance
“…Nevertheless, age appears to operate together with gender to shape experiences across diverse school and work settings (AAUW 2001;Connell 2000;McLaughlin, Uggen, and Blackstone 2008;Uggen and Blackstone 2004). What we know about young workers and sexual harassment comes primarily from three recent studies using quantitative survey data (Fineran 2002;Sears et al 2011;Uggen and Blackstone 2004; see also Fineran and Gruber 2009). These investigations concluded that many adolescents experienced some form of harassing behavior at work.…”
Section: Sexuality Age and Power In The Workplacementioning
confidence: 99%
See 3 more Smart Citations
“…Nevertheless, age appears to operate together with gender to shape experiences across diverse school and work settings (AAUW 2001;Connell 2000;McLaughlin, Uggen, and Blackstone 2008;Uggen and Blackstone 2004). What we know about young workers and sexual harassment comes primarily from three recent studies using quantitative survey data (Fineran 2002;Sears et al 2011;Uggen and Blackstone 2004; see also Fineran and Gruber 2009). These investigations concluded that many adolescents experienced some form of harassing behavior at work.…”
Section: Sexuality Age and Power In The Workplacementioning
confidence: 99%
“…These investigations concluded that many adolescents experienced some form of harassing behavior at work. Fineran (2002) and Sears, Intrieri, and Papini (2011) found girls who reported experiencing sexually offensive behaviors at work were significantly more upset than boys. Young women were also more likely than young men to label their experiences sexual harassment (Sears et al 2011).…”
Section: Sexuality Age and Power In The Workplacementioning
confidence: 99%
See 2 more Smart Citations
“…Yet another U.S. study of the relationship between sexual harassment and empathic bias examined men's sexual harassment toward women but not same-gender targets (Schweinle et al 2009). However, as one recent study on the sexual harassment victimization of U.S. young adults showed, men not only do experience harassment but such victimizations can impact their adjustment and maturity outcomes, and a "wimpy male" hypothesis was discussed by the authors for explanation (Sears et al 2011). With a large-scale random sample of Taiwanese middle school students, this study assessed the prevalence of peer sexual harassment victimization among both boys and girls in Taiwan, which is expected to provide a more accurate picture and advance the current understanding of this significant gender issue.…”
Section: Introductionmentioning
confidence: 99%